Anatomical knowledge retention in third-year nursing students - Narnaware, Yuwaraj; Neumeier, Melanie (My University, 2021)
Human anatomy and physiology are considered a cornerstone of any health related profession and serve as a pre requisite for future nursing courses and clinicals (McVicar et al., 2015). However, numerous studies suggest that students experience great difficulty in transferring the fundamental anatomical knowledge that they gain in the first year of their programs to future theory/clinical practice ( Gunay & Kilinc, 2018). Most of the knowledge transfer, loss and/or retention studies have been carried out in medical, allied health disciplines, and this has been assessed only in second year nursing students recently (Narnaware & Neumeier, 2020). This study seeks to determine the percent of anatomical knowledge retained by third year nursing students and determine the levels of knowledge retention in the body’s organ systems.
Narnaware, Y., & Neumeier, M. (2021a-poster presentation). Anatomical Knowledge Retention in Third-Year Nursing Students. Experimental Biology (EB)-21, The American Association for Anatomy (AAA) Virtual Conference, USA, April 27-30, 2021.
Keywords: knowledge retention; nursing students